Lifestyle of students of Medical University of Silesia, Katowice, Poland, in years 2005 and 2020 - Tomasz Szymon Klocek; Przemysław Witek; Patryk Wawrzonkowski; Aleksandra Binek; Nadia Woźniak; Łukasz Krzych (Śląski Uniwersytet Medyczny w Katowicach, 2022)
Introduction Lifestyle is a broad concept with a large impact on health. It changes over time under the influence of scientific reports, social trends and individual conditions. The aim of this study was to make an intergenerational comparison of the lifestyle of students of the Medical University of Silesia, Katowice, Poland. Material and methods A cross-sectional study was conducted using the author's own questionnaire. Two groups of 221 subjects each, medical students in 2003-2005 and 2020, participated in the study. Recommendations of the World Health Organization were used to assess lifestyle and the variables were classified as "healthy" or "unhealthy". Results The students in 2020 exhibited "healthier" behaviors compared to the students in 2003-2005 in terms of the regularity of meals (p = 0.02), less frequent consumption of meals with a high salt content (p = 0.03), more frequent consumption of fruits and vegetables (p < 0.01) and longer sleep periods (p < 0.01). In contrast, caffeine use (p = 0.02), the frequency of alcoholic beverage consumption (p = 0.04) and the number of people experiencing stress (p < 0.01), which was destabilizing for most (p < 0.01), increased. Conclusions The lifestyle of medical students improved over 15 years in terms of eating habits. Unfavorable changes are related to alcohol consumption and perceived stress.